Analisis Kalimat Efektif pada Teks Esai dengan Tema Komunikasi serta Ekspresi pada Website “Kompasiana” Edisi Februari 2025 sebagai Bacaan Edukasi dalam Kehidupan Sosial - Elyna Rafiza Zaliana; Naura Lutfia Fajriani; Angela Merici Tamara Wibowo; Farah Maulida Ayu Zahara; Salma Ayu Aini Zulfa; Asep Purwo Yudi Utomo; Riyadi Widhiyanto; Vina Nur Indah Sari (BADAN PENERBIT STIEPARI PRESS, 2025)
Language reflects the identity of a tribe or region through its speech patterns and structure. With its uniqueness and richness, language conveys messages and hopes. When used in accordance with the speaker's intent, its fulfills its communicative function. A well-constructed sentence not only adheres to grammatical rules but also conveys a clear message and strengthens the argument. This study aims to analyze the use of effective sentences in essay texts and identify the factors that influence their effectiveness, so that readers can clearly understand what the writer has written. This research employs a descriptive qualitative approach and syntactic analysis to examine the use of effective sentences in essay texts on the